Development of Video-Based Teaching Materials for Swimming Learning - Farizal Imansyah; Widya Handayani; Jujur Gunawan Manullang (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2022)
The low learning outcomes in learning swimming causes lecturers to have creativity to develop and utilize Information and Communication Technology in learning activities. The purpose of this research is to produce teaching materials based on learning videos and the potential effects of teaching materials so that students are able to learn independently and not be boring. The research method used was development (Development Research). The research subjects were 28 students who took part in the learning process of the Swimming Learning course. The data collection technique used a questionnaire. Data analysis using simple statistics. The results showed that there was an increase in student learning outcomes after using swimming learning videos. Thus, the learning video developed is suitable for use in swimming learning.